Advanced characterization of albumin adsorption on a chemically treated surface for osseointegration: An innovative experimental approach. (June 2022) - Barberi, Jacopo; Ferraris, Sara; Giovannozzi, Andrea Mario; Mandrile, Luisa; Piatti, Erik; Rossi, Andrea Mario; Spriano, Silvia
Graphical abstract: Highlights: Characterization techniques are need for study protein adsorption on rough biomaterials. Albumin adsorption is investigated on polished and surface modified Ti6Al4V by new methods. Kelvin probe force microscopy allows imaging of the adsorbed protein layer. Protein structure was studied by surface enhanced Raman scattering and ζ potential. OH surface groups density determines the amount and conformation of protein adsorbed. Abstract: Surface chemistry, charge, wettability, and roughness affect the adsorbed protein layer, influencing biocompatibility and functionality of implants. Material engineering seeks innovative, sensitive, and reliable characterization techniques for study the adsorbed proteins. These techniques must be suitable to be directly used on the surfaces of clinical interest. In this paper, the characterization of surfaces with topography and chemistry developed for osseointegration is performed by innovative surface analysis techniques to investigate the properties of adsorbed bovine serum albumin. Ti6Al4V alloy chemically treated with an oxidative process to obtain peculiar surface features (roughness and surface hydroxylation) was tested and compared with mirror-polished titanium. Albumin forms a continuous layer on both Ti surfaces when adsorbed from near physiological concentrations, as proved by Kelvin force probe microscopy. It was observed that the hydroxylation degree plays a pivotal role in determining the conformation of proteins after adsorption, where it strongly drives protein unfolding, as confirmed by Surface Enhanced Raman scattering, and in influencing the mechanism and chemical stability of protein-surface interactions, which was highlighted by zeta potential titration curves.